2013
DOI: 10.1017/s0007114513002341
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementary calcium phosphate on plasma gastrointestinal hormones in a double-blind, placebo-controlled, cross-over human study

Abstract: Gastrointestinal hormones and Ca are associated with bone metabolism. The objective of the present human study was to determine the effect of calcium phosphate on the postprandial circulation of gastrointestinal hormones. A total of ten men participated in the present double-blind, placebo-controlled, cross-over study. The participants were divided into two groups. Of these, one group consumed bread enriched with 1 g Ca (pentacalcium hydroxy-triphosphate, CaP) daily for 3 weeks. The other group consumed placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
(50 reference statements)
2
11
1
Order By: Relevance
“…The absolute concentration of GLP-2 is not easy to establish as different techniques (ELISA, RadioImmunoAssay) have different sensitivities and give different results. Average normal circulating levels have variously been reported as 0.1 ng/ml [ 44 ] or 42pg/ml by RIA [ 45 ] , and 0.4ng/ml [ 46 ] or 30pg/ml by ELISA [ 47 ], and importantly the manufacturers of the ELISA we used report normal concentrations with a lower limit of 3.6 ng/ml, so overall the concentrations in our participants were probably low. Our findings would be consistent with a primary endocrine failure of GLP-2 synthesis rather than a failure of end-organ responsiveness (which would be expected to result in elevated GLP-2 levels).…”
Section: Discussionmentioning
confidence: 87%
“…The absolute concentration of GLP-2 is not easy to establish as different techniques (ELISA, RadioImmunoAssay) have different sensitivities and give different results. Average normal circulating levels have variously been reported as 0.1 ng/ml [ 44 ] or 42pg/ml by RIA [ 45 ] , and 0.4ng/ml [ 46 ] or 30pg/ml by ELISA [ 47 ], and importantly the manufacturers of the ELISA we used report normal concentrations with a lower limit of 3.6 ng/ml, so overall the concentrations in our participants were probably low. Our findings would be consistent with a primary endocrine failure of GLP-2 synthesis rather than a failure of end-organ responsiveness (which would be expected to result in elevated GLP-2 levels).…”
Section: Discussionmentioning
confidence: 87%
“…7 The present findings indicate that this does not result in upregulation of these peptides when fasted. Supporting this, others have reported that 1000 mg of calcium supplementation for 3 weeks does not influence fasting concentrations of total GLP-1 or GLP-1 41 although postprandial concentrations were enhanced, suggesting that the acute response that we previously reported 7 translates into chronic adaptation manifesting in the postprandial state.…”
supporting
confidence: 80%
“…A small clinical study compared the postprandial plasma concentrations of GLP-1 and GLP-2 between a group that had previously consumed calcium phosphate-enriched diet for 3 weeks and a control group. The study showed that postprandial GLP-1 and GLP-2 levels were significantly increased in the group that had calcium phosphate-enriched diet, whereas levels of insulin and glucose showed no differences between the groups (121). …”
Section: Gastrointestinal Hormonesmentioning
confidence: 99%